Association of nucleated red blood cells and severity of encephalopathy in normothermic and hypothermic infants. (7th December 2012) - Walsh, BH; Boylan, GB; Dempsey, EM; Murray, DM
Abstract Aim To determine whether hypothermia alters the discriminative ability of postnatal nucleated red blood cells (NRBCs) to distinguish between mild and moderate/severely encephalopathic infants. Methods A prospective cohort study recruited full‐term neonates with hypoxic ischaemic encephalopathy (HIE) from 2003 to 2012 (prehypothermic and hypothermic eras). The NRBC count was analysed in the first 24 h in all infants and compared between normothermic and hypothermic cohorts. The severity of encephalopathy was categorized using both clinical Sarnat score and continuous multichannel EEG. Results Eighty‐six infants with HIE were included: in the normothermic group, 19 were clinically mild, 24 moderate/severe; in the hypothermic group, 22 were mild, 21 moderate/severe encephalopathy. NRBC count discriminated between mild and moderate/severe Sarnat scores in the normothermic group (p = 0.03) but not in the hypothermic group (p = 0.9). This change was due to a decrease in NRBCs among moderately encephalopathic infants in the hypothermic cohort. Conclusion Postnatal NRBCs distinguished between mild and moderate/severe encephalopathy in normothermic infants but not in infants undergoing therapeutic hypothermia. We advise caution when using postnatal blood samples to study diagnostic biomarkers for HIE without first analysing the potential impact of hypothermia upon these markers.